A Robust Routing Strategy for Efficient Reallocation in Multi-Grid Environment - Sivasubramanian, R; Arthi, K (International Journal of Engineering and Technology, 2018)
Grid Computing is becoming the rising procedure in this ongoing condition. System figuring is the social affair of PC resources from various territories to accomplish a run of the mill objective. The framework can be considered as a spread structure with non-instinctive workloads that incorporate innumerable, the multi-grid environment which provides the multi-tenancy startup for the multiple inputs that is transmitted in the form of the data. The routing strategy which provides the robust reallocation in the grid environment. This paper proposes a Strategic Multi-Reallocation procedure which makes the reallocation in the multi-grid environment. We Propose the Grid-Hadlock Algorithm for the efficient reallocation in the multi-grid environment. The implementation proves the maximum occupancy and its reallocation strategies more efficient. The experimental results proves the phenomenon is more efficient.Â Â